Exploring the Link between Entrepreneurial Leadership and Innovation Success: Evidence from Small and Medium Enterprises - Putri, Viajeng Purnama; Fuadiputra, Iqbal Ramadhani; Ikhram W, M Abdi Dzil (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This study investigates the impact of entrepreneurial leadership on innovation performance, focusing on the mediating roles of innovation processes and products in small and medium enterprises (SMEs). Design/Methods/Approach: Data were gathered from 105 SME employees through purposive sampling and analyzed using the Structural Equation Model (SEM) with Partial Least Squares (PLS). Findings: Reveal that entrepreneurial leadership significantly influences innovation performance. The innovation process and products also play crucial roles in enhancing innovation performance. Additionally, entrepreneurial leadership positively affects the innovation process and products, which, in turn, mediate its relationship with innovation performance. These results highlight the importance of strengthening innovation processes and products to optimize the impact of entrepreneurial leadership. SMES should prioritize leadership development while balancing process and product innovation for sustainable growth. Lastly, innovative products can partially address process deficiencies, but an integrated approach is essential for long-term success. Originality/Value: The research provides a unique contribution by integrating multiple factors (leadership, innovation processes, and products) rather than analysing them in isolation. In addition to SEM-PLS, the FsQCA methodology is employed, which offers a more nuanced analysis than traditional methods. It focuses on a specific regional context and provides localised insights for business growth. Practical/Policy implication: The study provides actionable insights for SME leaders, emphasizing leadership training, R&D investment, and process efficiency. These are sensible recommendations that can be applied in real-world settings. Also, by highlighting the role of leadership in innovation, the research adds value to entrepreneurial strategy and organizational management literature. The study suggests a holistic approach integrating leadership, product innovation, and process improvement, paving the way for future research on external factors (e.g., policies and market conditions) affecting SME innovation.